AKTIVITAS ANTIBAKTERI DARI EKSTRAK JAMUR LAUT - Fadilah, Nur; Erawati, Erawati; Nahar, Hendrik; Dewanto, Didit Kustantio (Sekolah Tinggi Perikanan dan Kelautan (STPL) Palu, 2016)
A search new antibacterial compounds should continue to be done as a raw material of antibiotics. The purpose of this study, which is to get kind of marine fungi antibacterial activity and get the value of MIC and MBC. The study was conducted from the sampling sponge, marine fungi isolation, extraction, preparation of test bacteria, antibacterial activity testing and analysis of MIC and MBC. Data was analyzed by measuring the diameter of inhibition zone are formed. The results obtained, that debris ethanol fraction from marine fungi J3 can inhibit the growth of E. coli and S. aureus at a concentration of 100 mg/L to 100.000 mg/L. At the debris ethyl acetate fraction able to inhibit concentration of 1.000 mg/L to 100.000 mg/L. At the filtrate ethyl acetate fraction was able to inhibit 10.000 mg/L to 100.000 mg/L. For both types of test bacteria, MIC and MBC values are indicated by the highest debris ethanol fraction and lowest by the fraction of ethyl acetate filtrate.